Eksplorasi etnomatematika dalam menentukan hari sakral di Keraton Kasepuhan Cirebon - Arwanto, Arwanto; Lusiyana, Desy (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
Education and culture are two inseparable elements and even mutually support one another. Because culture is a unified whole and is one of the factors that influeence the existence of education, It even applies in a society and education is a fundamental need for every individual in society, Ethomatematics exists to bridge the gap between culture and education, especially in learning mathematics. The purpose of  this study was to determine the pattern of calsulating sacred days and their relation to learning mathematics.  This reseach is a qualitative type with an ethographic approach method. The data obtained from the results of inteviews with informants, namely expert figures in determining sacred day at the Kasepuhan Palace in Cirebon. Based on the rearch results obtained, there is a pattern for calculating sacred days by adding up the naktu or value of the year, day, market and mont, each of which has a different naktu or value. One of the mathematical elements contained in the pattern of calculating sacred day is the concept of addition and modulo aritmatic. So that the results of the exploration can be linked to the concept of mathematical material.